Using self-made digital audio recordings in the EFL classroom - Mohd Rasip, Norhayati (2011)
The importance of listening activities in language learning can hardly be denied. Teachers have used various devices to provide listening activities for their students. For institutions which are not equipped with language labs, teachers will normally use the portable cassette or CD player which are heavy and limited in storing huge amount of recordings. However, with the advancement of technology, keeping these recordings in MP3 files is possible through digital media. In terms of learning process, students are able to copy and keep these MP3 files through their pen-drives and later practice listening at home. Therefore, the demonstration will start off by explaining why teachers should consider using self-made audio recordings via the digital recorder. It is an alternative to improve the audio recordings mechanism via the digital mode. The practicality and flexibility in use will enable teachers to record various texts both authentic and self-made. Among the suggested recordings are radio or TV excerpts of news, speeches, talk shows and songs. This will be followed by steps on how to create their own recording materials for the English language activities. This presentation is useful for teachers who wish to incorporate listening activities in their classrooms and at the same time looking for a device which is practical and economical in storing massive number of recordings.